Vic‐Tricarbonyl Compounds of Quinolines: Analogues of Ninhydrin: A Short Review. (31st January 2019) - Ijaz, Fatima; Shafqat, Syed Salman; Ahamd, Hafiz Adnan; Munawar, Munawar Ali; Khan, Misbahul Ain
Abstract : Derivatives of ninhydrin are extensively used in the field of forensic sciences as important latent fingerprint reagents. Many works have been performed upon their synthesis and reactivity, but there are many spaces to work on the compounds of quinoline‐2, 3, 4(1 H )‐triones—analogues of ninhydrin, in both dimensions: synthesis and reactivity, and according to the best of our knowledge, not a single detailed or short compiled article has been published for these compounds. This review briefly summarizes the chemistry of quinoline‐2, 3, 4(1 H )‐triones. Abstract :